DAMPAK MEDIA SOSIAL (FACEBOOK) DAN GADGET TERHADAP MOTIVASI BELAJAR - Mariskhana, Kartika (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
ABSTRACT Mts Al Makmur Parungpanjang is the first junior high school to promote Islamic religious education and general knowledge. In MTs Al Makmur parungpanjang there is a phenomenon that concerns educators in schools and also parents where in the daily life of the wider community is well known ie social media (facebook) and gadgets. This study aims to test and analyze how big the impact of social media (facebook) and gadgets on student motivation in MTs Al-Makmur Parungpanjang. The survey method used in this study is by random sampling and calculate the questionnaire results that have been filled by students  by using slovin formula, where there are population for class VIII as many as 202 students and from that number obtained sample of 135 students. The results showed that social media (facebook) and gadgets impact simultaneously on students' motivation in MTs Al Makmur parungpanjang. The conclusion of this research is social media (facebook) and gadget is electronic media which become means in obtaining various information, both in the interest of education and also outside of education. Social media (facebook) and gadgets also contribute to the formation of the mindset and behavior of students in learning activities and activities outside the school, so it can be the attention of the school to its students to see the pattern of increased or decreased student learning motivation, therefore the required power better efforts of the school and parents as supervisors of student activities in order to create a good generation. Keywords: Social Media (facebook), Gadget and Student Motivation